2015
DOI: 10.15282/jmes.8.2015.23.0145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on the Mechanical Properties and Failure Behavior of Spot Welded Low Carbon Steel

Abstract: In this research, the effect of spot welding parameters on weld quality was investigated. The main affecting welding parameters such as weld current, weld time, electrode force and holding time were determined as the basis for quality evaluation. The selected quality features were classified into mechanical properties and failure behavior, which were required for application with highly dynamic loading. The peak load as one of the important mechanical properties, as well as the two distinct failure modes which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Exploration of new materials has a high impact in the study of change in strain, especially when subjected to high velocity impact [1][2][3]. Changing strain at high velocity impact affects the material's energy absorption and prevents the occurrence of fracture failure [4][5][6][7]. The magnesium alloy is characterized as a lightweight material and has high energy absorption capability.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of new materials has a high impact in the study of change in strain, especially when subjected to high velocity impact [1][2][3]. Changing strain at high velocity impact affects the material's energy absorption and prevents the occurrence of fracture failure [4][5][6][7]. The magnesium alloy is characterized as a lightweight material and has high energy absorption capability.…”
Section: Introductionmentioning
confidence: 99%
“…The used to regression models, analysis of variance and other statistics methods of their data, based on an experimental design by Taguchi method, making it possible to identify which parameters would significantly influence their responses [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However in vehicle manufacturing sequence, it is vital to achieve high quality welds which depends on the type of welding, welding parameters, mechanical properties of welded metal, all of which influences the metallurgical and thermal behaviour of the material during welding process [4]. Investigation on the effects of process parameters on mechanical properties of spot welded low carbon steel indicated that welding current has a major influence on the mechanical property of a welded metal due to the thermal load resulting from current flow through the electrode which depending on the current increases the heat input [5], thereby inducing thermal stress on the weldment. Prior to technological advancement in production and manufacturing process in early 1920s, Tungsten Inert Gas (TIG) welding processes had not gain much popularity because it was a grey area that required further development but its application and relevance in many industries in recent times have increased significantly due to cost savings and reliability [6].…”
Section: Introductionmentioning
confidence: 99%